PENGARUH IMPLEMENTASI PROGRAM PENINGKATAN MUTU MADRASAH TERHADAP KINERJA GURU DI MTS NEGERI KABUPATEN KAMPAR - H. Husaini (POTENSIA: Jurnal Kependidikan Islam, 2018)
The performance of the teacher can also be used by the individual for himself, looking at his self-image and self-esteem and reading from others in relation to his academic abilities and achievements, studying in school, making schoolwork, and rewarding his achievements. Study on implementation of madrasah quality improvement program in Kampar District proposed the problems are: 1) implementation of student quality improvement program at MTs Negeri in Kampar District; 2) the implementation of madrasah quality improvement program on teacher performance at MTs Negeri in Kampar District; 3) the implementation concept of madrasah quality improvement program on teacher performance at MTs Negeri in Kampar District. The result of the study that can be writweet is implementation of school intensity improvement program on teacher performance of MTs Negeri in Kampar District is moderate with percentage of 63,83% there is significant change between supervisor performance for teacher with influence equal to 0,489.